An Analysis of Symbolic Meaning on Jaran Pejanggik Dance - Fahrurrozi; Lela rahmawati; Yuda Januar Pratama (CV Insan Kreasi Media, 2022)
Jaran Pejanggik dance is performed as a thanks giving for sasak tribe community especially for parents whose son will be circumcised. The aim of this study is to describe the symbolic meaning of Jaran Pejanggik dance in traditional circumcision ritual of Sasak ethnic group, Pejanggik village, Praya Central District, Middle Lombok Regency, West Nusa Tenggara. This study uses descriptive method because the data collected in this study are in the form of images and words, not numbers. In gathering the data, this research used metode simak (observing method). A qualitative approach is the workings of research that emphasizes data deepening aspects in order to get the quality of the results of a study Based on the data reviewed, in most cases Jaran Pejanggik dance has as symbolic meaning in the range of simple motion in circumcision ritual Sasak ethnic group in Pejanggik Village, are as follows: 1). A man in his world will always have lose ground whether economically, in cultural and many facets of life that he will get success, 2). A lot of trials and obstacles have to be faced by human beings even sometimes the temptation of many ways might be misleading, life will not always be smooth in positive or negative way, 3). Humans must have been struck by disaster, obstacles and obstructions in life, when a tidal wave that never stops bumpy, but if the waves of life passed with enough courage, patience and granting advices, then all obstacles can be passed, 4). Circling clockwise a sekenam is a symbol that Islam has six pillars of faith that must be maintained by the Muslims under any circumstances. The symbolic Meaning of Jaran Pejanggik Dance is connoted as a journey of life and hope in the future, which is always related to Islam. Keywords: Symbolic Meaning, Jaran Pejanggik Dance, circumcision ritual of Sasak ethnic group